Anthropogenic N deposition alters soil organic matter biochemistry and microbial communities on decaying fine roots. (14th August 2019) - Argiroff, William A.; Zak, Donald R.; Upchurch, Rima A.; Salley, Sydney O.; Grandy, A. Stuart
Abstract: Fine root litter is a primary source of soil organic matter (SOM), which is a globally important pool of C that is responsive to climate change. We previously established that 20 years of experimental nitrogen (N) deposition has slowed fine root decay and increased the storage of soil carbon (C; +18%) across a widespread northern hardwood forest ecosystem. However, the microbial mechanisms that have directly slowed fine root decay are unknown. Here, we show that experimental N deposition has decreased the relative abundance of Agaricales fungi (−31%) and increased that of partially ligninolytic Actinobacteria (+24%) on decaying fine roots. Moreover, experimental N deposition has increased the relative abundance of lignin‐derived compounds residing in SOM (+53%), and this biochemical response is significantly related to shifts in both fungal and bacterial community composition. Specifically, the accumulation of lignin‐derived compounds in SOM is negatively related to the relative abundance of ligninolytic Mycena and Kuehneromyces fungi, and positively related to Microbacteriaceae. Our findings suggest that by altering the composition of microbial communities on decaying fine roots such that their capacity for lignin degradation is reduced, experimental N deposition has slowed fine root litter decay, and increased the contribution of lignin‐derived compounds from fine roots to SOM. The microbial responses we observed may explain widespread findings that anthropogenic N deposition increases soil C storage in terrestrial ecosystems. More broadly, our findings directly link composition to function in soil microbial communities, and implicate compositional shifts in mediating biogeochemical processes of global significance. Abstract : Experimental nitrogen deposition (ca. 20 years) has slowed fine root decay and increased soil carbon across a widespread northern hardwood forest ecosystem, but the microbial mechanisms underlying this response are unknown. Here, we show that experimental N deposition has reduced the relative abundance of ligninolytic fungi and increased that of bacteria with weaker ligninolytic capacity on decaying fine root litter. These responses are correlated with an accumulation of lignin‐derived compounds in soil organic matter, of which fine root litter is the primary source. Thus, anthropogenic nitrogen deposition may enhance terrestrial carbon storage by altering microbial community composition on decaying fine roots.